Temporal trend of anisometropia incidence in Chinese school-aged children before and during the COVID-19 pandemic - Huang, Yin; Qiu, Kunliang; Li, Yuancun; Wang, Hongxi; Zhang, Mingzhi (Frontiers in Medicine, 2024)
Objective To analyze and compare the temporal trends in the incidence of anisometropia among Chinese school-aged children both before and during the COVID-19 pandemic, and to investigate the impact of the pandemic on the incidence of anisometropia. Methods We conducted a retrospective study comprising six distinct and independent longitudinal cohorts, each including children aged 6 to 13 years who visited the Joint Shantou International Eye Center between January 2010 and December 2021. Children were grouped into cohorts based on the year of their first eye clinic visit: 2010, 2012, 2014, 2016, 2018, or 2020. Only children without anisometropia at initial visits, followed for 18±6 months, were included. The cumulative incidence and risk factors of anisometropia were analyzed using Kaplan-Meier estimation and Cox proportional hazards regression models. Subgroup analyses were performed based on sex, age groups, initial refractive error status, and initial interocular SE difference. Anisometropic children were further categorized into myopic and non-myopic, with subsequent subgroup analyses conducted. Results Of 11,235 children were recruited from six cohorts (2010: n = 1,366; 2012: n = 1,708; 2014: n = 1,896; 2016: n = 2,354; 2018: n = 2,514; 2020: n = 1,397), 869 children developed anisometropia during a mean follow-up of 17.5 ± 3.7 months. After adjustment of confounding factors, we found that the risk of anisometropia remained relatively stable before 2020 but significantly increased in the 2020 cohort (adjusted HR 2.93 (95% CI 2.23 to 3.86; p<0.001). This trend persisted in studies of spherical anisometropia (adjusted HR 2.52, 95% CI 1.60 to 3.97; p<0.001) and cylindrical anisometropia (adjusted HR 2.91, 95% CI 1.69 to 3.62; p<0.001). Older age and a greater initial difference in SE between the two eyes were also significantly associated with a higher risk of developing anisometropia (p<0.001). Subgroup analyses consistently showed increased risk in the 2020 cohort. Conclusion This study reveals a concerning rise in anisometropia incidence among Chinese school-aged children during the period of the COVID-19 pandemic. These findings highlight the worrisome rise in anisometropia risk during the COVID-19 pandemic and emphasize the importance of early detection and management to safeguard children's visual health.